2014
DOI: 10.3109/02770903.2014.930879
|View full text |Cite
|
Sign up to set email alerts
|

Indoor environmental factors associated with wheezing illness and asthma in South Korean children: phase III of the International Study of Asthma and Allergies in Childhood

Abstract: Although the risk factors for current asthma appear to be more related to the non-modifiable risk factors like sex, parental history of allergic diseases, SPT, the two groups are associated with exposure to modifiable indoor environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Interestingly, boys are more likely to have certain atopic diseases in childhood, including rhinitis and asthma. 38,39 This gender difference provides some evidence of an association between ATH and allergies. A cohort study showed that boys exhibited higher interferon-gamma, interleukin (IL)-5, and IL-13 responses, indicating different cytokine responses and suggesting that these elevated responses might lead to sex-specific atopic characteristics during childhood.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, boys are more likely to have certain atopic diseases in childhood, including rhinitis and asthma. 38,39 This gender difference provides some evidence of an association between ATH and allergies. A cohort study showed that boys exhibited higher interferon-gamma, interleukin (IL)-5, and IL-13 responses, indicating different cytokine responses and suggesting that these elevated responses might lead to sex-specific atopic characteristics during childhood.…”
Section: Discussionmentioning
confidence: 93%
“…Overall, 91 studies in Asia investigated the associations between the family history of various allergy-related diseases and the risk of asthma development [ 20 , 22 , 23 , 25 27 , 31 , 32 , 34 36 , 42 , 44 46 , 51 , 52 , 57 , 59 , 62 , 65 – 68 , 70 – 73 , 76 79 , 82 140 ]. Among these, the family medical history of asthma (any family members) was most frequently studied and significantly associated with an increased risk of asthma (36 studies) [ 20 , 25 27 , 32 , 34 , 35 , 44 46 , 51 , 57 , 59 , 76 , 77 , 79 , 82 , 83 , 86 , 95 , 101 , 102 , 104 – 106 , 108 110 , 112 , 116 , 123 , 128 , 129 , 133 , 137 , 140 , 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…The association between gender and asthma was reported in 75 studies [ 16 , 18 , 19 , 21 , 22 , 33 , 35 , 37 , 38 , 40 , 42 , 43 , 47 , 49 , 56 , 58 , 62 , 67 , 70 , 71 , 73 , 74 , 79 , 82 87 , 92 , 93 , 95 , 97 , 99 , 104 , 105 , 107 , 110 , 116 , 118 , 120 , 122 , 124 127 , 130 , 131 , 133 , 135 137 , 139 , 142 , 159 , 170 , 179 , 184 201 ]. Of these, 58 studies have observed male subjects having a higher asthma susceptibility as compared with that of the female subjects significantly [ 16 , 18 , 22 , 37 , 38 , 40 , 47 , 56 , 58 , 62 , 67 , 70 , 71 , 73 , 74 , …”
Section: Resultsmentioning
confidence: 99%
“…We also found that boys had significantly higher total IgE levels than girls. Boys are more likely to have a number of atopic diseases such as rhinitis and asthma in childhood (2324). A birth cohort study showed distinctive patterns of cytokine responses between girls and boys (13).…”
Section: Discussionmentioning
confidence: 99%